Nicorandil in patients with acute myocardial infarction undergoing primary percutaneous coronary intervention: a systematic review and meta-analysis. - Muli Wu; Zheng Huang; Haojun Xie; Zhongjiang Zhou (PLoS ONE, 2013)
Background Nicorandil, as an adjunctive therapy with primary percutaneous coronary intervention (PCI), had controversial benefits in cardioprotection in patients with acute myocardial infarction (AMI). Methods and results We performed a systematic review of randomized controlled trials (RCTs) comparing treatment with nicorandil prior to reperfusion therapy with control (placebo or no nicorandil) in patients who suffered from AMI and performed primary PCI. PubMed, EMBASE and CENTRAL databases and other sources were searched without language and publication restriction. 14 trials involving 1680 patients were included into this meta-analysis. Nicorandil significantly reduced the incidence of thrombolysis in myocardial infarction (TIMI) flow grade ≤ 2 (risk ratio [RR], 0.57; 95% confidence interval [CI]: 0.42 to 0.79), the Timi frame count (TFC) (mean difference [MD], -5.19; 95% CI: -7.13 to -3.26), increased left ventricular ejection fraction (LVEF) (%) (MD, 3.08; 95% CI: 0.79 to 5.36), and reduced the incidence of ventricular arrhythmia (RR, 0.53; 95% CI: 0.37 to 0.76) and congestive heart failure (CHF) (RR, 0.41; 95% CI: 0.22 to 0.75). No difference in the pear creatine kinase (CK) value (MD, -290.19; 95% CI: -793.75 to 213.36) or cardiac death (RR, 0.39; 95% CI: 0.09 to 1.67) was observed. Conclusions Nicorandil prior to reperfusion is associated with improvement of coronary reflow as well as suppression of ventricular arrhythmia, and further improves left ventricular function in patients who suffered from AMI and underwent primary PCI. But the definite clinical benefits of nicorandil were not found, which may be due to the small sample size of the selected studies.